THE MELANCHOLIC GAZES IN THE GRAPHIC NOVEL THE MAGIC FISH : OS OLHARES MELANCÓLICOS NA GRAPHIC NOVEL THE MAGIC FISH - de Araujo Placido, Carlos Eduardo (Miscelânea: Revista de Literatura e Vida Social, 2024)
Le Nguyen, received several nominations for important awards such as the GLAAD Awards and the Lambda Literary Awards. The author Le Nguyen used a plethora of artistic resources from the sequential narratives to tell different experiences of his protagonists as mother and son, Hiền and Tiến Phong, with the Fall of Saigon and the discovery of the son’s queerness as an immigrant in the United States of America. Many of these experiences were embodied through the various representations of the melancholic gaze. For these reasons, this article intended to discuss the characteristics of the melancholic gazes through The Magic Fish (2020)’s sequential narratives. As a result, various representations of gazing, looking, and wandering were identified about the protagonists’ painful reminiscences during the Fall of Saigon and their current challenges to live as queer immigrants. ABSTRACT: The semi-autobiographical graphic novel The Magic Fish (2020), by the American-Vietnamese cartoonist Trung